2022
DOI: 10.1007/s11356-022-24910-9
|View full text |Cite
|
Sign up to set email alerts
|

Ecological distribution of modern diatom in peatlands in the northern Greater Khingan Mountains and its environmental implications

Abstract: Relationships between diatoms assemblages and environmental variables in peatlands of the northern Greater Khingan Mountains is helpful for understanding the indicative signi cance of diatoms to environment changes, and potentially provides a reference for environmental monitoring and paleoenvironment reconstruction in the edge of monsoon region. In this study we analyzed modern diatom distribution and explored the relationships between diatoms assemblages and 11 environment factors in 30 shrubby-herbaceous an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…The most frequently encountered species in the moderate fen, Pinnularia pulchra and Eunotia pseudoparallela , are described as epipelic in oligotrophic waters with low electrolyte content in East Greenland and northern Finland and are reported as absent from Europe [ 44 ]. Han et al [ 82 ] found P. pulchra as one dominant diatom species in herbaceous peatlands in the northern Greater Khingan Mountains, China, tolerant of neutral-alkaline habitats. Likewise, the moderate fen conditions align as suitable to support P. pulchra .…”
Section: Discussionmentioning
confidence: 99%
“…The most frequently encountered species in the moderate fen, Pinnularia pulchra and Eunotia pseudoparallela , are described as epipelic in oligotrophic waters with low electrolyte content in East Greenland and northern Finland and are reported as absent from Europe [ 44 ]. Han et al [ 82 ] found P. pulchra as one dominant diatom species in herbaceous peatlands in the northern Greater Khingan Mountains, China, tolerant of neutral-alkaline habitats. Likewise, the moderate fen conditions align as suitable to support P. pulchra .…”
Section: Discussionmentioning
confidence: 99%
“…Their short life span and sessile traits enable them to capture ephemeral environmental variations at sampling sites. Moreover, their sensitivity to multiple environmental factors and nutrient enrichment endows characterizing species in terms of functional categories, e.g., salinity, pH, oxygen demands, nitrogen assimilation, and trophic status (Desrosiers et al, 2013;Han et al, 2023).…”
Section: Introductionmentioning
confidence: 99%